2007
DOI: 10.4049/jimmunol.179.2.984
|View full text |Cite
|
Sign up to set email alerts
|

IL-4 and IL-13 Negatively Regulate TNF-α- and IFN-γ-Induced β-Defensin Expression through STAT-6, Suppressor of Cytokine Signaling (SOCS)-1, and SOCS-3

Abstract: Human β-defensins (HBDs) are a major class of antimicrobial peptides that play an important role in the innate immune response, however, the induction and regulation of these antimicrobial peptides is not well understood. We demonstrate here that stimulation of keratinocytes with TNF-α/IFN-γ induces HBD-2 and HBD-3 by activating STAT-1 and NF-κB signaling. We further demonstrate that IL-4 and IL-13 activate STAT-6 and induce the suppressors of cytokine signaling (SOCS)-1 and -3. This interferes with STAT-1 and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
163
0
5

Year Published

2008
2008
2022
2022

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 181 publications
(181 citation statements)
references
References 41 publications
13
163
0
5
Order By: Relevance
“…Addition of IL-4 to a Th1 cytokine mixture led to inhibition of hBD2 in keratinocytes (33). This is in line with our findings and that of other investigators using IL-4 in KC (45,46).…”
Section: Discussionsupporting
confidence: 92%
“…Addition of IL-4 to a Th1 cytokine mixture led to inhibition of hBD2 in keratinocytes (33). This is in line with our findings and that of other investigators using IL-4 in KC (45,46).…”
Section: Discussionsupporting
confidence: 92%
“…STAT6 is a Th2-associated transcription factor that is activated through phosphorylation and that translocates into the nucleus during the activation of M2 macrophages (47). Previous studies have demonstrated that helminth infections or the treatment with their ES products led to significant M1-to-M2 macrophage transition, which is dependent on activation of the STAT6 signaling (25,48).…”
Section: Discussionmentioning
confidence: 99%
“…Both GM-CSFR and IL-4R signal through JAK/STAT pathways several members of which are direct substrates for SHP-1. IL-4 signaling leads to activation of STAT-6, which is required for IL-4-mediated inhibition of TNF-a production (30,52). Furthermore, SHP-1 has been shown to directly inhibit STAT-6 phosphorylation (29,53), suggesting that this may be the mechanism by which SHP-1 inhibition augments IL-4-mediated TNF-a inhibition.…”
Section: Discussionmentioning
confidence: 99%